MODIFIKASI COVER MENJADI INFRARED WINDOW MOTOR 362-MD1 UNTUK INSPEKSI THERMOGRAPH - Hamdi Hamdi; Junjung Dwi Laksana Aji (Politeknik Negeri Jakarta, 2018)
ABSTRACTThermograph is recognized as one of the best methods for identifying problems with low, medium and high voltage electrical equipment. Thermograph is used as a qualitative and quantitative tool. Qualitative visual shaped images on Thermograph and quantitative infrared cameras in the form of temperature range. In the inspection Thermograph should open the cover of the motor so the danger that arises in Arc Flash Explosion, the danger of rotating equipment and the danger of flying carbon powder. Arc Flash Explosion events generally occur in high equipment because of defective tools or human error. Arc Flash Explosion will not occur without a trigger, with changes in pressure and temperature can cause a short circuit. Arc Flash Explosion occurs when an undesired electrical current flows through the air due to the accumulation of carbon powder, thus heating the air and causing an explosion. When the inspector is not equipped with a personal protective equipment located near Arc Flash. As a result inspector injury and even death. So it is necessary to develop a device for Thermograph inspection security that can separate two environments with different pressures and temperatures. The danger of rotating equipment and the danger of carbon powder flying. IR Window is a security device for Thermograph inspection. Because with the pair IR Window can provide assurance from the Arc Flash Explosion, the danger of rotating equipment and carbon powder hazards that fly because it does not open the motor cover. Thus, Thermograph inspectors can safely complete inspection without process interruption, faster, reduce the number of workers and more completed inspection so as to reduce the risk of equipment failure through routine monitoring techniques and prediction techniques.Keywords: Thermograph, IR Window (InfraRed Window), Arc Flash ExplosionABSTRAKThermograph sebagai salah satu metode terbaik untuk mengidentifikasi masalah pada peralatan listrik tegangan rendah, menengah dan tinggi. Thermograph digunakan sebagai alat inspeksi kualitatif secara visual berbentuk gambar pada kamera infrared Thermograph dan kuantitatif berbentuk range suhu. Dalam inspeksi Thermograph harus membuka cover motor sehingga bahaya yang ditimbulkan yaitu Arc Flash Explosion, bahaya benda yang berputar dan bahaya serbuk karbon yang berterbangan. Peristiwa Arc Flash Explosion pada umumnya terjadi pada peralatan tegangan tinggi karena alat rusak ataupun kesalahan manusia. Arc Flash Explosion tidak akan terjadi tanpa adanya pemicu, dengan perubahan tekanan dan suhu dapat menyebabkan hubung singkat. Arc Flash Explosion terjadi ketika arus listrik yang tidak diinginkan mengalir melalui udara karena adanya akumulasi serbuk karbon, sehingga memanaskan udara dan menyebabkan ledakan. Ketika inspektor tidak dilengkapi dengan alat pelindung diri berada di dekat Arc Flash. Akibatnya inspektor mengalami cedera bahkan kematian. Sehingga perlu mengembangkan perangkat untuk keamanan inspeksi Thermograph yang dapat memisahkan dua lingkungan dengan tekanan dan suhu yang berbeda. Bahaya benda yang berputar dan bahaya serat karbon yang berterbangan. IR Window adalah perangkat keamanan untuk inspeksi Thermograph. Karena dengan di pasangnya IR Window dapat memberikan jaminan dari Arc Flash Explosion, bahaya benda berputar dan bahaya serbuk karbon yang berterbangan karena tidak membuka cover motor. Dengan demikian, inspektor Thermograph dapat menyelesaikan inspeksi dengan aman tanpa gangguan proses, lebih cepat, mengurangi jumlah pekerja dan lebih banyak inspeksi selesai sehingga dapat mengurangi risiko kegagalan peralatan melalui teknik pemantauan rutin dan teknik prediksi.Kata kunci: Thermograph, IR Window (InfraRed Window), Arc Flash Explosio